Discovery of populations of the critically endangered coral Rhizopsammia wellingtoni in the Galápagos mesophotic zone - Robert Wellington Lamb; Alejandro Pérez‐Matus; Vladimir Garmendia; Jenifer Suarez‐Moncada; Marcelo Tite Ortega; Stuart Banks; Nathalia Tirado Sanchez; Anna Dubey; Jon D. Witman (Conservation Science and Practice)
Abstract Wellington's solitary coral, Rhizopsammia wellingtoni, has not been documented since 2006 in the Galápagos Islands, leading to its designation as a critically endangered species by the IUCN due to declining populations and a risk of extinction. We surveyed 12 sites throughout the Galápagos archipelago in July–August 2024 using technical diving with rebreathers and discovered abundant populations of R. wellingtoni living in the mesophotic zone at depths of 50–60 m at three locations. Densities of 2.0, 5.3, and 64.9 corals per square meter were recorded at Cabo Douglas, Cuatro Hermanos, and Guy Fawkes, respectively. Video transects conducted at 10 m depth intervals above 50 m failed to encounter any corals. Size structure varied considerably: 74% of the corals found at the southernmost site of Cuatro Hermanos were large colonies composed of multiple polyps, while 26% were solitary individuals. In contrast, the northernmost site of Guy Fawkes had a predominance of solitary individuals (60%) with larger multi‐corallite colonies accounting for only 40% of corals, suggesting a younger population and high recruitment at this site. Historical records from Tagus Cove, where R. wellingtoni was first described in large abundance and at shallow depth, suggest that the species experienced significant declines between 1976 and 1999—a period that included the anomalously warm 1982–1983 El Niño event, which is attributed to have caused this species to decline to its current distribution. The apparent restriction of current R. wellingtoni populations to depths greater than 50 m where temperature remains below 17°C is consistent with the hypothesis that this species achieved a refuge in depth from exceptional shallow warming during past El Niño events. As the impacts of climate change intensify, further exploration of mesophotic zones using advanced diving methods will be crucial for evaluating potential extinctions and for conserving marine biodiversity.